2005
DOI: 10.1098/rsbl.2005.0330
|View full text |Cite
|
Sign up to set email alerts
|

Different hunting strategies select for different weights in red deer

Abstract: Much insight can be derived from records of shot animals. Most researchers using such data assume that their data represents a random sample of a particular demographic class. However, hunters typically select a non-random subset of the population and hunting is, therefore, not a random process. Here, with red deer ( Cervus elaphus ) hunting data from a ranch in Toledo, Spain, we demonstrate that data collection methods have a significant influence upon the apparent relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 11 publications
(18 reference statements)
3
76
0
Order By: Relevance
“…For mountain sheep, Coltman et al (2) showed that harvest of trophy rams led to selection for lighter and smaller-horned rams. Different hunters invoke different methods in being selective, and Martínez et al (73) argued that the urge for hunters to kill males with large antlers and to maximize opportunity to be selective by hunting early in the season were primary motivations. Mysterud et al (74) found that hunter type (local vs. ''foreign'') provided substantial variation in terms of temporal and spatial components of hunting activity, and that although the activities of the different hunter types influenced the relationship between age and antler mass, much of this influence arose from variation in the timing and location of hunting.…”
Section: Huntingmentioning
confidence: 99%
“…For mountain sheep, Coltman et al (2) showed that harvest of trophy rams led to selection for lighter and smaller-horned rams. Different hunters invoke different methods in being selective, and Martínez et al (73) argued that the urge for hunters to kill males with large antlers and to maximize opportunity to be selective by hunting early in the season were primary motivations. Mysterud et al (74) found that hunter type (local vs. ''foreign'') provided substantial variation in terms of temporal and spatial components of hunting activity, and that although the activities of the different hunter types influenced the relationship between age and antler mass, much of this influence arose from variation in the timing and location of hunting.…”
Section: Huntingmentioning
confidence: 99%
“…If harvest probability is affected by regulations for minimum size, gear selectivity [13] or by cultural preferences, the average size of harvested animals should be greater than the population average. These biases have been acknowledged [14], but it remains unknown how they affect our ability to detect temporal trends in phenotypic traits.…”
Section: Introductionmentioning
confidence: 99%
“…Sit-and-wait hunting at agricultural fields in morning and evening is common during weekdays for local hunters in between work, whereas drive hunting is more common during weekends when also nonresidents are hunting. It is well known that differences in hunting methods also affect selectivity (27). This points to the potentially important aspects of culture and to fruitful future applications of our framework.…”
Section: Discussionmentioning
confidence: 75%